Two idea(l)s of the international rule of law. Issue 2 (13th June 2019) - COLLINS, RICHARD
Abstract: The international rule of law is a somewhat ubiquitous concept yet, as idea, it is marred by ambiguity and disagreement and, as ideal, constantly frustrated by the institutional conditions of the decentralised international legal order. Rather than necessarily undermining the concept, however, I argue that these structural conditions cause a kind of conceptual rupture, resulting in seemingly opposed or contradictory idealisations. On the one hand, the international rule of law can be understood as what Terry Nardin has called the 'basis of association' in international relations. This understanding places importance on the legal form as an end in itself, whereby the structural or institutional autonomy of international law is critical to the peaceable conduct of international relations. On the other hand, however, the rule of law exists as an unfulfilled promise of an order to come: it is distinctly anti-formalist in nature, stressing the functional capacity of international law to actually constrain political actors (primarily states) and thus seeking to develop more effective international institutional mechanisms. Although these competing idealisations give rise to a certain contradiction and inherent tension, their conceptual opposition is, I believe, critical to an understanding of authority and accountability dynamics in an era of 'global governance'.